2023
DOI: 10.1039/d3ob01015e
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted DABCO-promoted regioselective [3 + 3] tandem cyclization: synthesis of pyrrolo[3,4-b]pyridine-4-ones from trifluoromethyl-alkynyl esters and α-aminomaleimide

Abstract: A microwave-assisted DABCO-promoted strategy for the regioselective synthesis of pyrrolo[3,4-b]pyridine-4-ones derivatives has been developed from the [3 + 3] annulation of α-aminomaleimide with substituted ethyl 2-butynoate. The characteristic features of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In our investigation of organic reactions using ethyl lactate (EL) as a solvent, we observed that the classical conversion of EL involves dehydrogenating its alcohol fragment to ethyl pyruvate. 18 Building on this transformation and our group's expertise in synthesizing nitrogen-containing heterocyclic compounds from imine intermediates, 19 we developed a novel approach for directly synthesizing pyrimidines from EL. This sustainable method involves capturing ethyl pyruvate generated in situ by EL through iron( iii )-catalyzed formation of quaternary ammonium salts from inorganic NH 4 I and benzaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…In our investigation of organic reactions using ethyl lactate (EL) as a solvent, we observed that the classical conversion of EL involves dehydrogenating its alcohol fragment to ethyl pyruvate. 18 Building on this transformation and our group's expertise in synthesizing nitrogen-containing heterocyclic compounds from imine intermediates, 19 we developed a novel approach for directly synthesizing pyrimidines from EL. This sustainable method involves capturing ethyl pyruvate generated in situ by EL through iron( iii )-catalyzed formation of quaternary ammonium salts from inorganic NH 4 I and benzaldehyde.…”
Section: Introductionmentioning
confidence: 99%